2020
DOI: 10.1007/s42773-020-00048-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochar characterization of invasive Pennisetum purpureum grass: effect of pyrolysis temperature

Abstract: Pennisetum purpureum is one of the most invasive perennial grasses of the Poaceae family, which are abundant in southeast Asia including Brunei Darussalam. The pyrolysis process at a slow heating rate proved to be highly promising for biochar production. The production and characterization of different Pennisetum purpureum biochars have been investigated at the pyrolysis temperatures of 400 °C, 500 °C and 600 °C with a heating and nitrogen flow rate of 5 °C/min and 0.5 L/min, respectively. The observed higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 108 publications
10
43
0
Order By: Relevance
“…Although it has been shown that larger charcoal particles originate generally within a few hundred metres of a lake archive (Clark et al, 1998;Higuera et al, 2007;Ohlson and Tryterud, 2000), they have also been observed to travel further depending on vegetation and fire conditions (Peters and Higuera, 2007;Pisaric, 2002;Tinner et al, 2006;Woodward and Haines, 2020). As wildfires in the Siberian boreal forest are predominantly considered low-intensity surface fires (de Groot et al, 2013;Rogers et al, 2015), the potential of the resulting convection to transport large charcoal particles is probably limited compared to high-intensity crown fires. We therefore assume a charcoal source area between a few hundred metres directly around the lake for low-intensity fires (Conedera et al, 2009) and increasing distance of up to several kilometres for more intense fires producing stronger convection, resulting in a total source area estimate of up to ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been shown that larger charcoal particles originate generally within a few hundred metres of a lake archive (Clark et al, 1998;Higuera et al, 2007;Ohlson and Tryterud, 2000), they have also been observed to travel further depending on vegetation and fire conditions (Peters and Higuera, 2007;Pisaric, 2002;Tinner et al, 2006;Woodward and Haines, 2020). As wildfires in the Siberian boreal forest are predominantly considered low-intensity surface fires (de Groot et al, 2013;Rogers et al, 2015), the potential of the resulting convection to transport large charcoal particles is probably limited compared to high-intensity crown fires. We therefore assume a charcoal source area between a few hundred metres directly around the lake for low-intensity fires (Conedera et al, 2009) and increasing distance of up to several kilometres for more intense fires producing stronger convection, resulting in a total source area estimate of up to ca.…”
Section: Discussionmentioning
confidence: 99%
“…Aakala et al, 2018;Feurdean et al, 2017;Molinari et al, 2020;Wallenius, 2011). However, comparisons across boreal study sites are complicated by the differing predominant fire regimes in North America (high-intensity crown fires) and Eurasia (lower-intensity surface fires) (de Groot et al, 2013;Rogers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonaceous materials are prepared by eliminating the volatile matters through thermal decomposition in this stage. Temperature, heating rate, gas flow rate, and the residence period are the main parameters [17]. As biochars show lower adsorption capability, an activation procedure is important to develop the pore volume and the surface areas.…”
Section: Preparation Of Acmentioning
confidence: 99%
“…Solid oxide fuel cell (SOFC) offers relatively very high competence among all the types of fuel cells, fuel flexibility (hydrogen, natural gas, biogas from biomass [28][29][30][31][32], and gases made from coal), and low emissions, which led to the use of SOFCs as future power generation technology [33,34]. It shows high efficiency (>60% efficiency) with clean environment credentials [35].…”
Section: Introductionmentioning
confidence: 99%